Health inequalities among the elderly in western Europe. Issue 6 (13th May 2008) - Rueda, S; Artazcoz, L; Navarro, V
Abstract : Background: This paper analyses gender inequalities in health status and in social determinants of health among the elderly in western Europe. Methods: Data came from the first wave of the "Survey of Health, Ageing and Retirement in Europe" (2004). For the purposes of this study a subsample of community-residing people aged 65–85 years with no paid work was selected (4218 men and 5007 women). Multiple logistic regression models separated by sex and adjusted for age and country were fitted. Results: Women were more likely to report poor health status, limitations in mobility and poor mental health. Whereas in both sexes educational attainment was associated with the three health indicators, household income was only related to poor self-rated health among women. The relationship between living arrangements and health differed by gender and was primarily associated with poor mental health. In both sexes, not living with their partner but living with other people and being the household head was related to poor mental health status (adjusted odds ratio (aOR) 2.14; 95% CI 1.11 to 4.14 for men and aOR 1.75; 95% CI 1.12 to 2.72 for women). In addition, women living with their partner and other(s) and those living alone were more likely to report poor mental health status (aOR 1.67; 95% CI 1.17 to 2.41 and aOR 1.58; 95% CI 1.26 to 1.97, respectively). Conclusions: Health inequalities persist among the elderly. Women have poorer health status than men and in both sexes the risk of poor health status increases among those with low educational attainment. Living arrangements are primarily associated with poor mental health status with patterns that differ by gender.